OCT Angiography as an Interdisciplinary Diagnostic Tool for Systemic Diseases OCT-Angiografie als interdisziplinäres Diagnostikum für Systemerkrankungen - Hohberger, Bettina; Mardin, Christian Y. (Klinische Monatsblätter für Augenheilkunde, 2021)
In recent years, OCT angiography (OCT-A) has emerged as a well established imaging modality of the retina. This allows non-invasive visualisation of the retinal circulation at a micrometer scale in eye disorders and systemic diseases with potential ocular involvement. This review summarises the current state of this topic.
CRIS-Team Scopus Importer:2021-12-24
Keywords: capillary; COVID-19; microcirculation; OCT-angiography; SARS-CoV-2; vessel density